The Influence of Product Quality, Brand Image, and Brand Trust on Avoskin Serum Purchasing Decisions in National University Students - Fitri Handayani; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of Product Quality, Brand Image, and Brand Trust on the Purchase Decision of Avoskin Serum among female students at the National University. The sample in this study were 100 female students at the National University who had purchased avoskin serum products. This study uses primary data by collecting data through questionnaires distributed to 100 respondents, using a purposive sampling method. The data analysis technique uses the Partial Least Squares Path Modeling (PLS-SEM) 3.3.2 program. This shows that Product Quality (X1) has a positive and significant effect on Purchasing Decisions (Y), Brand Image (X2) has a positive and significant effect on Purchase Decisions (Y), Brand Trust (X3) has a positive and significant effect on Purchase Decisions (Y ). So it can be concluded that product quality, brand image, and brand trust have a positive and significant effect on purchasing decisions.